Graft : architecture activism - Zerelli, Nora; Korner, Christoph; Putz, Wolfram; Willemeit, Thomas, 1968- (Birkhäuser Verlag GmbH, 2016)
Founded in Los Angeles in 1998, GRAFT is a global architectural practice which now maintains branches in Berlin and Beijing. The international practice, which is involved in architectural, urban, and product design - as well as branding - is known for its experimental and interdisciplinary designs as well as for its strong social commitment. The publication will document only projects characteristic of this social responsibility - it portrays architecture as an active tool for driving, in a global context, the development of places worth living in. One key project is the Solar Kiosk developed in 2012, a high-output, solar-based unit which is already used by many communities in Sub-Saharan Africa to secure their power supply.